Repair of Temporal Bone Defects via the Middle Cranial Fossa Approach: Treatment of 2 Pathologies With 1 Operation. Issue 6 (17th May 2018) - Eddelman, Daniel B; Munich, Stephan; Kochanski, Ryan B; Eggerstedt, Michael; Kazan, Robert P; Moftakhar, Roham; Munoz, Lorenzo; Byrne, Rich W; Wiet, R Mark
Abstract: BACKGROUND: Temporal bone dehiscence (TBD) often results in leakage of cerebrospinal fluid (CSF) and/or encephalocele. TBD can also occur over the superior semicircular canal, causing debilitating vertigo. Both can be repaired surgically, but traditional treatment is focused only on one pathology, not both. OBJECTIVE: To report our experience in the treatment of TBD via the middle cranial fossa (MCF) approach. METHODS: A retrospective review was conducted for all patients who underwent MCF approach for surgical repair of any temporal fossa dehiscence. RESULTS: A total of 34 patients underwent a total of 37 surgeries. Obesity was prevalent; 21 patients (61.8%) were obese (BMI [body mass index] > 30 kg/m 2 ), and 7 (20.6%) were overweight (BMI 25-30 kg/m 2 ). The most common presenting symptom was hearing disturbance (70.3%), followed by otorrhea (51.4%). Empty sella was noted on computed tomography or magnetic resonance imaging in 15 patients (45.5%). Eight of the 34 patients (23.5%) were found to have superior semicircular canal dehiscence (SCD). Hearing improved with surgical intervention in 25 of 26 patients with hearing loss as a presenting symptom (96%). CSF resolved in 18 of 19 cases (95%). Seventy-three percent of patients reported at least minimal improvement in vertigo. CONCLUSION: TBD may present with symptoms of CSF leak/encephalocele, but may also present with superior SCD. We recommend consistent review of the temporal bone imaging to check for superior SCD, and repair of the SCD first to prevent complications involving the labyrinth and cochlea. MCF approach using a multilayer repair without a lumbar drain is highly effective with minimal risk of complications.